OTIMIZAÇÃO DA EXTRAÇÃO DE COMPOSTOS BIOATIVOS DAS FOLHAS DE Campomanesia sessiliflora (O. BERG) MATTOS. - LOUREIRO, Raquel Parra,; CASTRO, Thiago Luis Aguayo,; CARDOSO, Claudia Andrea Lima, (ANAIS DO ENIC, 2025)
.